Alchornea Fluviatilis: uma nova euphorbiaceae da Amazônia - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 1993)
A new species of the genus Alchornea SW (Euphorbiaceae) is developed and illustrated. One species is called Alchornea Alchornea R. Secco, speaker characterized by the ovary 3-4-5, short to medium stylets (4-7mm). rudimentary stamens in the calyx of the pistillate flower, bisexual inflorescence, polymorphous and deciduous leaves in flowering. Its affinities with Alchornea discolor Poepp are discussed.
Keywords: Alchornea; Euphorbiaceae of Amazonia; Alchornea fluviatilis; Alchornea discolor; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA